Perceived Performance of Persons with Disabilities and Work Design - Maria Nivalda de Carvalho-Freitas; Raissa Pedrosa Gomes Tette; Graceane Coelho de Souza; Daiane Rose Cunha Bentivi; Marcos Santos de Oliveira (Revista Psicologia)
The aim of the present research was to evaluate the predictive power that the factors of work design have about the perception that colleagues and managers have regarding the performance of people with disabilities. The sample consisted of 72 employees (including teachers and administrative technicians) from a federal public university, who answered the sociodemographic questionnaire, the Work Design Questionnaire (WDQ), and the Inventory of Perceived Performance in the Work Environment. In addition, semi-structured interviews were conducted with 20 employees. It was verified that autonomy in planning tasks, the variety of tasks, identification of the task and the physical demands explain 40% of the variation of the perceived performance of people with disabilities in the context investigated. These results indicate that work design has an essential role in the perceived performance of people with disabilities, extending the empirical evidence about the possible performance of these people, thus supporting a more inclusive labor market.